Children's consumer socialisation agents in India. (1st January 2014) - Chaudhary, Monica; Gupta, Aayushi
The paper titled 'Children's consumer socialisation agents in India' has two objectives: to identify and rank the important consumer socialisation agents among Indian children and to examine the impact of various socialisation agents on child's influence level in the family buying process. The empirical study is based on an extensive literature review and focus group discussions. Through structured questionnaires, a survey has been conducted with children (aged 8–12 years). As per the findings through regression analysis, the consumer socialisation agents: television, internet and parents emerged as a significant predictor of child's role as co-decision maker in the purchase decisions for the three product categories. The study has made much needed contribution to the extant literature on Indian children in the age-group 8–12 years as consumer. The findings would add value to marketing companies and practitioners to have a better understanding of Indian children's influence behaviour. The identified socialisation agents are expected to add clarity to the issue of children's role in family decision-making. Marketers should take these observations into consideration while designing and implementing global sales promotion and advertising strategies.